Aplikasi Sistem Informasi Geografis (SIG) Untuk Pemetaan Tingkat Kerawanan Longsor Di Kota Bandar Lampung - Jihan Syafina Nasution (Progressive Physics Journal, 2025)
The research entitled "Geographic Information System (GIS) Application for Landslide Prone Level Mapping in Bandar Lampung City" is motivated by data obtained from BPBD in 2018, there are at least 15 sub-districts in Bandar Lampung which are indicated as landslide-prone areas because they have hills and valleys that are quite dangerous. For this reason, it is necessary to create a landslide prone zone map to produce information about the position related to the level of landslide vulnerability in the city of Semarang. This map can be used as a reference material in decision making to prevent landslides in vulnerable areas, thus reducing the number of casualties and material as well as planning in the development of facilities and infrastructure. This research uses remote sensing image data and GIS (Geographic Information System) by weighting the parameters that affect landslide occurrence, namely: slope, land cover, soil type, and rainfall. The result of this research is a landslide vulnerability map divided into 4 vulnerability classes, namely: low, medium, high, and very high. And the information obtained from the 4 factors, the potential for landslides in Bandar Lampung City is divided into 4 characteristics of landslide prone zones, namely low level zones in 7 sub-districts, medium level in 9 sub-districts, high level in 5 sub-districts, and very high level in 7 sub-districts.